2023
DOI: 10.3390/antibiotics12030467
|View full text |Cite
|
Sign up to set email alerts
|

Green Antimicrobials as Therapeutic Agents for Diabetic Foot Ulcers

Abstract: Diabetic foot ulcers (DFU) are one of the most serious and devastating complications of diabetes and account for a significant decrease in quality of life and costly healthcare expenses worldwide. This condition affects around 15% of diabetic patients and is one of the leading causes of lower limb amputations. DFUs generally present poor clinical outcomes, mainly due to the impaired healing process and the elevated risk of microbial infections which leads to tissue damage. Nowadays, antimicrobial resistance po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 101 publications
0
4
0
Order By: Relevance
“…Compared with the direct use of traditional wound microenvironment regulation (anti-inflammatory and antioxidant), pro-angiogenesis and antibacterial drugs, [12][13][14] the application of wound repair based on nanomaterials and nano-drug delivery systems [15][16][17] shows superior therapeutic prospects. This is because the latter may have the following advantages and effects: [18][19][20] the multienzyme and other multifunctional activities of the nanocomplex itself; the special properties of nanocarriers of good drug loading and release in response to the a Center for Pharmaceutical Formulation and Nanomedicine Research, College of microenvironment.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the direct use of traditional wound microenvironment regulation (anti-inflammatory and antioxidant), pro-angiogenesis and antibacterial drugs, [12][13][14] the application of wound repair based on nanomaterials and nano-drug delivery systems [15][16][17] shows superior therapeutic prospects. This is because the latter may have the following advantages and effects: [18][19][20] the multienzyme and other multifunctional activities of the nanocomplex itself; the special properties of nanocarriers of good drug loading and release in response to the a Center for Pharmaceutical Formulation and Nanomedicine Research, College of microenvironment.…”
Section: Introductionmentioning
confidence: 99%
“…It is widely recognized that there is an urgent need to search for new therapies to replace or support the action of currently used antibiotics and antiseptics [ 17 ]. Nature itself is a reservoir of natural antimicrobial compounds that could be extracted mainly from plants, with one of the best examples being the essential oils that have received great acceptance in the pharmaceutical industry and consumers in the past years [ 20 , 21 , 22 , 23 ]. This fact is highlighted by the World Health Organization, which has reported that natural therapy is gaining increasing influence among the world’s population [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…This new search should have in mind not only the need for effective antibacterial products but also the need of sustainable sources of these products [ 24 ]. Environmental concerns are being discussed globally, and the pharmaceutical industry is under intense pressure to address the negative environmental effects that have resulted from the development and use of medications [ 3 , 21 ]. This worry is mostly caused by the amount of waste from the usage of medications that has been discovered in nature, including antiseptic residues.…”
Section: Introductionmentioning
confidence: 99%
“…Skin disorders have benefited immensely from natural-origin antimicrobials. Diabetic foot ulcers, for instance, have been shown to accelerate their healing in the presence of antimicrobial peptides derived from green, eco-friendly processes [10]. In chronic wound care, many antiseptic agents have also been highlighted, namely octenidine and polyhexamide, as beneficial for wound care without inducing any cytotoxic effects or raising significant environmental concerns [11].…”
mentioning
confidence: 99%